Synthesis And Characterization Of Gel Polymer Electrolyte And Zinc Oxide For Photoelectrochemical Cell - Alias, Siti Salwa (2011)

(untitled)
This project is divided into three sections: preparation and characterization of gel polymer electrolyte (GPE) based on commercial agar; synthesis and characterization of nanoparticles powders zinc oxide (ZnO); and fabrication of photoelectrochemical cell (PEC). The GPE was prepared by dissolving agar powder in glycerol. Various concentrations of ammonium iodide and iodine were added to the agar paste until an optimum conductivity was reached. The optimum conductivity of (2.64 ± 0.19) x 10-3 S cm-1 was obtained from a sample of agar paste with 1.0 M NH4I and 0.2 μM I2 (A1.0N0.2I). The A1.0N0.2I had the lowest viscosity values of (1.17 ± 0.29) Pa s. All GPEs showed Arrhenius behavior with the lowest activation energy value of 0.25 eV for A1.0N0.2I. A1.0N0.2I also showed good physical appearance.